1999
DOI: 10.1007/s002130050867
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin as a possible mediator of SSRI-induced antidepressant effects

Abstract: The nonapeptide oxytocin is released into systemic circulation in situations of psychosocial interaction, and has been shown to be involved in mechanisms of social bonding and social recognition in laboratory studies. In view of disturbances in psychosocial relationships being a triggering factor for depression and anxiety, it is interesting to note that experimental studies have shown oxytocin to possess antidepressant- and anxiolytic-like actions. Thus. in the present study we examined effects of the SSRI ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 35 publications
1
76
1
2
Order By: Relevance
“…Since the CSF oxytocin levels were not normally distributed, log transformation was applied prior to statistical analyses to achieve normal distribution. Because previous studies suggest that some antipsychotic and antidepressant medications increase oxytocin secretion (Uvnas-Moberg et al, 1992;Uvnas-Moberg et al, 1999), chlorpromazine and imipramine equivalent doses were examined as possible confounders. Statistical analyses were performed using the Statistical Package for the Social Sciences version 11.0 (SPSS Japan, Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…Since the CSF oxytocin levels were not normally distributed, log transformation was applied prior to statistical analyses to achieve normal distribution. Because previous studies suggest that some antipsychotic and antidepressant medications increase oxytocin secretion (Uvnas-Moberg et al, 1992;Uvnas-Moberg et al, 1999), chlorpromazine and imipramine equivalent doses were examined as possible confounders. Statistical analyses were performed using the Statistical Package for the Social Sciences version 11.0 (SPSS Japan, Tokyo, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin fibers project to the raphe nuclei and OT may influence the secretion of 5-HT. Recent studies have demonstrated that OT is released in response to treatment with selective serotonin reuptake inhibitors (SSRI), opening up the possibility that OT also mediate further effects caused by serotonin (Uvnas-Moberg et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on the inhibitory influence of OT on stress-responsive neurohormonal systems focused on the endogenous stimulation of OT during lactation in rodents. The suckling stimulus by the newborn was found to increase OT release and decrease basal plasma levels of ACTH and cortisol [26,27,121,148,149,160].…”
Section: Social Stress and Anxietymentioning
confidence: 98%